The quills of the porcupine : Asante nationalism in an emergent Ghana - Allman, Jean Marie (University of Wisconsin Press, 1993)
The porcupine is the national symbol of the Asante. This is a case study in the social history of African politics. Placed in the context of so much theoretical and historical literature on class, ethnicity and nationalism, its significance is aimed beyond the borders of Asante, and Ghana.